Integração de banco de dados e modelos de simulação de culturas para estimular o impacto de mudanças do clima no rendimento de grãos e na severidade da giberela em trigo - Lazzaretti, Alexandre Tagliari (2013)
This study aimed to use database technology, integrated with crop models and epidemiological models, to estimate the impact of global climate change on yield and severity of giberela in wheat. For this, was created and implemented a generic project database system called AgroDB, which has the necessary characteristics for integration with crop models. As a case study the models used were Cropsim-Wheat and GIBSIM. We performed the evaluation and calibration of the crop model Cropsim-Wheat, in relation to yield and growth stages of wheat. In this sense, we used two conventional field experiments, performed in the years 2010 and 2011 in Passo Fundo to cultivars: BRS 177, BRS 194, BRS 276, BRS 296, BRS Louro, Guabiju, Guamirim and Timbaúva. To estimate potential impacts of global climate change on yield and severity of giberela, 54 experiments were simulated, corresponding to 27 stations in the state of Paraná. As for each location, used 30 years (1980-2009) of observed climate data and, 16 ensembles of 30 years (2070 to 2099) corresponding to the IPCC A2 scenario. The cultivar used in these experiments was the BRS Louro. It can be observed that the database AgroDB served as resource of integration, to perform the simulations, and data management, making the process fast and secure. In addition, you can perform the evaluation and calibration of the crop model Cropsim-Wheat regarding to growth stages and yield of wheat. It was found, through simulations, that global climate change scenarios (IPCC A2) increase the yield of wheat in the years 2070 to 2099 compared to years 1980 to 2009. Moreover, it was verified an increase in the severity of giberela in the years 2070 to 2099 compared to years 1980 to 2009, which can cause an alert about the control of disease and the quality of the grain of wheat that will be produced in the future